Exploring young children’s perspectives of inclusive education through the use of participatory research methods - Adderley, Rebecca Jane (Indonesian Journal of Early Childhood Education Studies, 2017)
This paper reports on two small scale research projects which were undertaken in the north east of England. The two projects engaged with pupils from the age of four up to the age of sixteen. However, it is only the children aged four to age seven whose views are going to be reported here. The studies aimed to listen to children’s views about how the practices of teachers helped or hindered their sense of inclusion in classrooms. Inclusion was understood here in a broad sense rather than specifically relating to children defined as having special educational needs. Participatory research tools were used as part of group interviews with children. The findings from this research are explored under four main thematic headings that relate specifically to teachers and teacher practices: characteristics and personality of the teacher; support and assistance that the teacher gives; the teacher’s use of discipline and finally the choices given to children by teachers. These themes are seen to be connected to each other under the broader headings of emotional support and instructional support and can be seen as crucial in terms of understanding inclusion in schools and further developing existing practices.